Analisis Pendekatan Konstruktivisme dalam Buku Arabiyyah Linnasyiin Karya Dr. Mahmud Ismail - Muhammad Naufal; Ahmad Rizki Nugrahawan (Penerbit Minhaj Pustaka, 2025)
This study aims to analyze the application of constructivism theory in the book Arabiyyah Linnasyiin Volume 2 by Dr. Mahmud Ismail, focusing on the four Arabic language skills (listening, speaking, reading, and writing) and the quality of teaching materials. The research used a qualitative approach with a content analysis method, reinforced by teacher interviews and student questionnaires as data triangulation. The research subjects include the book Arabiyyah Linnasyiin Volume 2, the Arabic language teacher of grade 2 of MTs An Najah, and 20 students of grade 2 of MTs An Najah who became respondents of the questionnaire. The results showed that the content of the book supported the theory of constructivism with positive achievements in the content analysis, the results of the teacher interview which stated that the book was suitable for use, and the results of the student questionnaire which showed a score of 33.4% on the constructivism indicator (good category) and 37.7% on the four language skills indicator (positive category). The study concluded that the book Arabiyyah Linnasyiin Volume 2 has good quality and is suitable for use as teaching materials for constructivism-based Arabic language learning that encourages active understanding, meaningful interaction, and the development of Arabic language skills as a whole. So that this research can provide an illustration that this book is still very relevant to be used in learning. Abstrak Penelitian ini bertujuan menganalisis penerapan teori konstruktivisme dalam buku Arabiyyah Linnasyiin Jilid 2 karya Dr. Mahmud Ismail, dengan fokus pada empat keterampilan bahasa Arab (mendengar, berbicara, membaca, dan menulis) serta kualitas bahan ajarnya. Penelitian menggunakan pendekatan kualitatif dengan metode analisis isi, diperkuat oleh wawancara guru dan angket siswa sebagai triangulasi data. Subjek penelitian meliputi buku Arabiyyah Linnasyiin Jilid 2, guru bahasa Arab kelas 2 MTs An Najah, serta 20 siswa kelas 2 MTs An Najah yang menjadi responden angket. Hasil penelitian menunjukkan bahwa konten buku mendukung teori konstruktivisme dengan capaian positif dalam analisis isi, hasil wawancara guru yang menyatakan buku layak digunakan, serta hasil angket siswa yang menunjukkan skor 33,4% pada indikator konstruktivisme (kategori baik) dan 37,7% pada indikator empat keterampilan bahasa (kategori positif). Penelitian menyimpulkan bahwa buku Arabiyyah Linnasyiin Jilid 2 memiliki kualitas baik dan layak digunakan sebagai bahan ajar pembelajaran bahasa Arab berbasis konstruktivisme yang mendorong pemahaman aktif, interaksi bermakna, dan pengembangan keterampilan berbahasa Arab secara menyeluruh